VD_FINDINFO ML / 2012 / 297 vom 4. Dezember 2012 - VD Tribunal cantonal (2012)
DÉLAI DE RECOURS, PROLONGATION DU DÉLAI, RESTITUTION DU DÉLAI, OBSERVATION DU DÉLAI | 144 al. 1 CPC (CH), 148 CPC (CH), 321 al. 1 CPC (CH)